Édouard Risler (1873 - 1929) et la musique française - Saint-Arroman, Gilles (Paris Champion, 2008)
Pianist Édouard Risler (1873-1929) was a central figure in French music at the turn of the 19th and 20th centuries. An interpreter of the greatest composers and creator of major scores (Bourrée fantasque by Chabrier, Sonate by Dukas, works by Saint-Saëns, Fauré, Hahn...), Risler maintained strong ties with Germany. This book follows the international career of a pianist torn between two cultures, reflecting the growing influence of the French school in its golden age. (Translated with DeepL.com)
Includes bibliographical references and index.
Keywords: Risler, Edouard -- 1873-1929; 19th Century (1801-1900); 20th Century (1901-2000); Music history; Pianist; Biography; France